AN EXPLORATORY OBSERVATION INTO THE STATUS OF COLLABORATIVE MANUFACTURING FOR TOOL AND DIE DEVELOPMENT IN MALAYSIA - Selvarajoo, Suman; Raja Ghazilla, Raja Ariffin; Mamat, Azuddin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
This research explores the current status of collaborative manufacturing for tool and die development in the Malaysian manufacturing industry. Collaborative manufacturing is one of the characteristics that contribute to Industrial Revolution 4.0. Therefore, it is crucial to improve the current status of collaborative manufacturing in the Malaysian industry. Factory visits were conducted to observe the practices of manufacturing companies that use tools and dies, and the data collected from the observations were analyzed and compared to understand the present status of the industry. The findings suggest that the local industries are not significantly different from the overseas industries in most areas. However, some issues need to be addressed, particularly in terms of technology, quality, and management, to further improve the current status of collaborative manufacturing. Most importantly, the management’s participation and initiatives are crucial in establishing an ideal collaborative environment.